(untitled) (Perner’s Contacts, 2011)
This paper discusses airport operational performance issue. The focus is on research executed to find out which areas need to be improved in the airport operations in near future. Also, features of IT solutions for achieving better process control and the overall performance are briefly described. This paper is a part of project “Centre of Excellence for Air Transport”ITMS 26220120065.